Burden of metabolic syndrome among primary care patients in Crete, Greece: A descriptive study. (16th December 2020) - Anastasaki, Marilena; Papadakis, Sophia; Linardakis, Manolis; Anyfantakis, Dimitrios; Symvoulakis, Emmanouil K.; Lionis, Christos; ,
Abstract: Background: Metabolic Syndrome (MetS) is a clustering of abdominal obesity, hypertriglyceridaemia, low HDL cholesterol, hyperglycaemia and hypertension. Early identification of MetS is important for preventing cardiovascular disease (CVD). MetS has not been systematically explored in Greek primary care. Objectives: To examine MetS frequency among primary care patients 40 years of age or older in Crete. Methods: A descriptive study was conducted (July–December 2015). General practitioners, randomly selected from regional physician listings, recruited consecutive patients, 40 years of age or older, visiting their practice. Chart audits were completed for eligible patients using medical records, including demographics and cardiovascular risk factors (hypertension, dyslipidaemia, diabetes mellitus). MetS was defined using the revised NCEP ATP III criteria. Frequencies with 95% confidence intervals were calculated. Gender differences were explored using Chi-square and Mann–Whitney tests. Results: Our sample consisted of 815 patients (55.7% female; mean age 65.2 years; range 40–98 years) from 44 GP practices. Overall, 73.6% (95% CI 70.4, 76.6) were identified with MetS, with a higher proportion of males (75.6%; 95% CI 71.0, 79.8) than females (72.0%; 95% CI 67.8, 76.0). Among the total sample, relatively high rates of hypertension (males: 64.5%; 95% CI 59.9, 70.0 and females: 61.1%; 95% CI 56.8, 65.8), dyslipidaemia (males: 69.3%; 95% CI 64.3, 74.1 and females: 63.5%; 95% CI 59.3, 68.0), diabetes mellitus (males: 46.9%; 95% CI 42.2, 52.4 and females: 36.5%; 95% CI 32.5, 41.6) and coronary heart disease (males: 21.2%; 95% CI 17.0, 25.2 and females: 6.2%; 95% CI 4.2, 8.6) were documented. Conclusion: MetS and CVD risk factors were encountered at high frequencies in the studied population of primary care patients in Crete.